2002
DOI: 10.1262/jrd.48.157
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Porcine Parthenogenetic Diploid Oocytes with Homogeneous Genomic Components In Vitro.

Abstract: Abstract. The aim of this study was to determine the influence of the homogeneity of genomic components and ploidy on the in vitro development of porcine parthenogenetic oocytes to the blastocyst stage. In vitro matured oocytes were subjected to a single pulse of electro-stimulation (El-St; 100 µsec, 1,500 V/cm) for activation. First, the activated oocytes were cultured for 6, 16, 18, 20 and 22 h after El-St, and examined for the timing of the first cleavage of parthenogenetic haploids. Next, the effects of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
(35 reference statements)
0
3
0
Order By: Relevance
“…With in vitro fertilization, high developmental ability to the blastocyst stage is hardy expected because of the high incidence of polyspermy in the pig. Our previous reports have shown that electroactivated porcine oocytes that had been matured in vitro can develop to the blastocyst stage in vitro; furthermore, the characteristics of development of porcine parthenogenetic diploids to the blastocyst stage resembled those of in vitro fertilized eggs [40][41][42][43]. These results suggested that parthenogenetic diploids could be used as model embryos instead of fertilized oocytes for studies regarding the early development and establishment of culture systems in the pig.…”
Section: Introductionmentioning
confidence: 81%
“…With in vitro fertilization, high developmental ability to the blastocyst stage is hardy expected because of the high incidence of polyspermy in the pig. Our previous reports have shown that electroactivated porcine oocytes that had been matured in vitro can develop to the blastocyst stage in vitro; furthermore, the characteristics of development of porcine parthenogenetic diploids to the blastocyst stage resembled those of in vitro fertilized eggs [40][41][42][43]. These results suggested that parthenogenetic diploids could be used as model embryos instead of fertilized oocytes for studies regarding the early development and establishment of culture systems in the pig.…”
Section: Introductionmentioning
confidence: 81%
“…In present study, parthenogenetic diploids were used due to the relatively high occurrence of polyspermy with in vitro fertilization of porcine embryos. However, the development of porcine parthenogenetic diploids to the blastocyst stage is comparable to the normal development of embryos [38][39][40] .…”
Section: Methodsmentioning
confidence: 92%
“…In the porcine system, a high incidence of polyspermy is seen with in vitro fertilization, and development to the blastocyst stage is compromised. However, development of porcine parthenogenetic diploids to the blastocyst stage resembles normal development (Kure-bayashi et al, 1996;Thuan et al, 2002;Cui and Kim, 2003). These results suggested that parthenogenetic diploids could be used as model embryos for studies regarding early development and establishment of in vitro culture systems in the pig.…”
Section: Introductionmentioning
confidence: 85%